Talking of many things: Using topical networks to study discussions in social media - Highfield, Tim (Taylor & Francis, 2012)
This article outlines a method for studying online activity using both qualitative and quantitative methods: topical network analysis. A topical network refers to “the collection of sites commenting on a particular event or issue, and the links between them” (Highfield, Kirchhoff, & Nicolai, 2011, p. 341). The approach is a complement for the analysis of large data sets enabling the examination and comparison of different discussions as a means of improving our understanding of the uses of social media and other forms of online communication. Developed for an analysis of political blogging, the method also has wider applications for other social media websites such as Twitter.